Importance of the loop at residues 230-245 in the allosteric interactions of Escherichia coli aspartate carbamoyltransferase. - Middleton, S A (1986)
Site-directed mutagenesis has been used to replace tyrosine-240 with phenylalanine in each of the catalytic chains of aspartate carbamoyltransferase. Tyrosine-240 is part of a loop in the structure of the enzyme, between residues 230 and 245, which undergoes a substantial conformation change as the enzyme becomes ligated [Krause, K. L., Volz, K. W. & Lipscomb, W. N. (1985) Proc. Natl. Acad. Sci. USA 82, 1643-1647]. The mutant enzyme with phenylalanine at position 240 has substantially reduced homotropic interactions and an increased affinity for the substrate aspartate but displays no alteration in maximal observed specific activity. The Hill coefficient decreases from 2.4 for the wild-type enzyme to 1.8 for the mutant, and the aspartate concentration at half the maximal observed velocity decreases from 11.9 mM to 4.7 mM at pH 8.3. Heterotropic interactions of the mutant enzyme are altered to a lesser extent. The catalytic subunit derived from the mutant enzyme exhibits kinetics identical to that of the wild-type catalytic subunit. Reactivity of the mutant enzyme with p-hydroxymercuribenzoate suggests that the unligated enzyme exists in an altered conformation. The properties of the mutant enzyme are explained in terms of the structure of the wild-type enzyme, and a model is proposed to account for the allosteric interactions of the wild-type enzyme in terms of specific interactions involving the 230-245 loop of the enzyme.